Enrichment of circulating trophoblasts from maternal blood using filtration-based Metacell® technology - Weymaere, Jana; Vander Plaetsen, Ann-Sophie; Van Den Branden, Yasmine; Pospisilova, Eliska; Tytgat, Olivier; Deforce, Dieter; Van Nieuwerburgh, Filip (PloS one, 2022)
In a cell-based non-invasive prenatal test (cbNIPT), intact circulating trophoblasts (CTs) are isolated from maternal blood for subsequent genetic analysis. Enrichment of these CTs from maternal blood is the most challenging step in the cbNIPT workflow. This study aims to assess the suitability of the filtration-based Metacell® technology to enrich CTs from maternal blood at week 10 to 13 of gestation. The Metacell® technology is a novel size-based enrichment technology that combines blood filtration through 8 μm pores with an in vitro culture method. Three protocols were evaluated. First, 8 mL or 16 mL of maternal blood was filtered and subsequently cultured in vitro on the separation membrane for 3 days in RPMI 1640. In addition, 16 mL of maternal blood was filtered, and immediately processed without further culturing. Y-chromosome-specific qPCR or STR analysis was performed to evaluate the enrichment of CTs. A total of 44 samples from pregnant women, out of which 26 were carrying a male fetus, were processed. Although five enriched male fetus samples show detectable male DNA quantities, it cannot be excluded that the obtained positive signal is caused by cell-free fetal DNA sticking to the Metacell® separation membrane. In conclusion, the Metacell® technology, tested as described, is not suitable for consistent enrichment of CTs.
Keywords: DNA; Pregnancy; Trophoblasts; těhotenství; Male; trofoblasty; plod; technologie; lidé; Female; mužské pohlaví; ženské pohlaví; Fetus; Prenatal Diagnosis; prenatální diagnóza; Humans; Technology